Medicinal Plant Images - Cock, I. E. (Pharmacognosy Communications)
The genus Rubus comprises around 700 species, naturally occurring in temperate climates. [ 1 , 2 ] Some of them are cultivated in numerous varieties as industrial plants for the quality of nutritious and tasty fruits. Rubus caesius is a well-known shrub belonging to Rosaceae family. It is also commonly known as dewberry, blackberry or bramble. It is native member of fl ora extending from Europe to Siberia, but it can be successfully found in the northcentral United States.